Decision Support System for Selecting Exemplary Students with Simple Additive Weighting Method - Nurahman Nurahman; Minarni Minarni; Nindi Ernawati Nindi Ernawati; Nadia Sari Nadia Sari (Politeknik Negeri Cilacap, 2023)
The selection of exemplary students carried out by the school is expected to trigger the enthusiasm of students to be able to develop their interests, talents, and abilities in the academic and non-academic fields. However, decision-making has not been measured with data so a decision support system is needed. With the use of this method, it is hoped that it can make it easier and minimize the occurrence of errors in making decent decisions therefore this system is needed to be able to make good decisions. In this study, one of the decision support system methods that are often used was chosen, namely Simple Additive Weighting (SAW). The use of the SAW method is due to its uncomplicated calculations. Research conducted at this school in determining decisions is still done manually so it is less effective and efficient. Therefore, this decision support system must be able to calculate exemplary students to be more effective and efficient. This system displays the final results of the ranking of exemplary students using the SAW method. From the overall results of the research that has been carried out, the calculation results that got rank 1 were obtained, namely Kenzo Ecclesio Taha with a total score of 0.9025. From the results of the study, it can be concluded that the results meet the criteria, so this study can be considered in calculations to determine exemplary students in the future